Proceedings Visualization '99 (Cat. No.99CB37067) 1999
DOI: 10.1109/visual.1999.809924
|View full text |Cite
|
Sign up to set email alerts
|

Real-time visualization of scalably large collections of heterogeneous objects

Abstract: This paper presents results for real-time visualization of out-of-core collections of 3D objects. This is a significant extension of previous methods and shows the generality of hierarchical paging procedures applied both to global terrain and any objects that reside on it. Applied to buildings, the procedure shows the effectiveness of using a screen-based paging and display criterion within a hierarchical framework. The results demonstrate that the method is scalable since it is able to handle multiple collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…Several blocks can be in a view, depending on the viewpoint location. We have found that this balance in size makes out-of-core data retrieval efficient for a variety of data [4,3].…”
Section: Dynamic and Synchronized Data Structuresmentioning
confidence: 99%
See 2 more Smart Citations
“…Several blocks can be in a view, depending on the viewpoint location. We have found that this balance in size makes out-of-core data retrieval efficient for a variety of data [4,3].…”
Section: Dynamic and Synchronized Data Structuresmentioning
confidence: 99%
“…Our system is built on our global geo-spatial data organization and visualization system, VGIS (Virtual Geographic Information System) [3,4,6]. VGIS treats the terrain as a single, connected surface for rendering using a continuous, view-dependent Level-Of-Detail (LOD) representation.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Out-of-core visualization techniques are applied to cope with massive data sets stored on external memory (Davis et al [5]; Lindstrom and Pascucci [14]). Techniques have been described for large-scale virtual environments such as described by Willmott et al [19] and for large-scale texture data.…”
Section: Real-time Rendering Of 3d City Modelsmentioning
confidence: 99%
“…Approximate occlusion-culling algorithms, such as [7], [8], [9], the visible primitives are rendered up to a specified threshold, i.e., some of them may not be sent to the graphics pipeline although they are visible. There are also approaches to occlusion culling that use parallel processing approaches, such as [10], [5], [11].…”
Section: Introductionmentioning
confidence: 99%